Geomechanical evaluation of rock masses in the left abutment and power house area at the Khao Laem Damsite - Dacha Luangpitakchumpol; Yudhbir; Tomiolo, Andrea; Prinya Nutalaya; Carl Duisberg Gesellschaft, e.V., Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1982)
Geomechanic evaluation was carried out on the rock mass at Power House Area, Spur No . 2 of the Left Abutment and some parts of Gallery 'C', Right abutment by using the Geomechanic Classification of Jointed Rock Mass. After the study, it was found that the rock at the Left abutment at Spur No. 2 and Power House Area is rather poor quality, while in the Gallery 'C', Right abutment is good. · Using Stereographic projection techniques, a guideline to adjust basic RMR for slopes has been proposed. On the basis of Geomechanical Classification results and available data, representative values of Shear Strength Parameters and modules of deformation are recommended. Due to limited nature of investigation, no definite conclusion is arrived at regarding the status of fault activity at the site.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M. Sc.) - Asian Institute of Technology, 1982
Keywords: Rock mechanics; Khao Laem Dam